2010
DOI: 10.1016/j.neuroscience.2010.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of intermittent social defeat stress on brain-derived neurotrophic factor expression in mesocorticolimbic brain regions

Abstract: Social defeat stress is an ethologically salient stressor which activates dopaminergic areas and, when experienced repeatedly, has long-term effects on dopaminergic function and related behavior. The mechanism for these long-lasting consequences remains unclear. A potential candidate for mediating these effects is brain-derived neurotrophic factor (BDNF), a neurotrophin involved in synaptic plasticity and displaying alterations in dopaminergic regions in response to various types of stress. In this study, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
95
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 59 publications
8
95
0
2
Order By: Relevance
“…These disparate findings raise the possibility that stress induced by shock paradigms preferentially affect hippocampal cytokines whereas stress induced by non-shock paradigms affect cytokines in both the hippocampus and the prefrontal cortex. Other differential responses of the hippocampus and prefrontal cortex to stress have been reported previously, notably a variety of stresses have been reported to increase brain-derived neurotropic factor mRNA and or protein levels within the prefrontal cortex (Bland et al, 2007;Fanous et al, 2010), but they were unchanged or decreased in subregions of the hippocampus (Smith et al, 1995;Barrientos et al, 2004;Pizarro et al, 2004). The greater sensitivity of hippocampal cytokine increases to shock stresses may be related to the reportedly larger density of microglia in the hippocampus than in the prefrontal cortex (Lawson et al, 1990), although potential mechanisms underlying the differential inflammatory responses to stress in the hippocampus and the prefrontal cortex remain to be clarified.…”
Section: Discussionmentioning
confidence: 51%
“…These disparate findings raise the possibility that stress induced by shock paradigms preferentially affect hippocampal cytokines whereas stress induced by non-shock paradigms affect cytokines in both the hippocampus and the prefrontal cortex. Other differential responses of the hippocampus and prefrontal cortex to stress have been reported previously, notably a variety of stresses have been reported to increase brain-derived neurotropic factor mRNA and or protein levels within the prefrontal cortex (Bland et al, 2007;Fanous et al, 2010), but they were unchanged or decreased in subregions of the hippocampus (Smith et al, 1995;Barrientos et al, 2004;Pizarro et al, 2004). The greater sensitivity of hippocampal cytokine increases to shock stresses may be related to the reportedly larger density of microglia in the hippocampus than in the prefrontal cortex (Lawson et al, 1990), although potential mechanisms underlying the differential inflammatory responses to stress in the hippocampus and the prefrontal cortex remain to be clarified.…”
Section: Discussionmentioning
confidence: 51%
“…In these studies, preventing BDNF production in dopaminergic regions or inhibiting BDNF/TrkB signaling in the nucleus accumbens reduced the anxiety toward former aggressors and induces strong antidepressive effects in rodent, predicting that TrkB inhibition may lead to antidepressant action in humans (7,12). In line with this observation, mice susceptible to stress-related anxiety and depression exhibit high levels of BDNF in the ventral striatum (13) and acutely stressed mice show a rapid and sustained increase in BDNF expression in the prefrontal cortex and in the hippocampus (14,15). In consequence, while inhibiting BDNF signaling may not lead to depression-like behaviors (16)(17)(18), reports have suggested that inhibiting TrkB signaling may in contrast be a therapeutic strategy for treating human mood disorders (5,7,13,19).…”
Section: Introductionmentioning
confidence: 85%
“…Overactivity of the BDNF/TrkB signaling in the reward circuitry, including striatum and cortex, and in the hippocampus has been associated with the development of anxiety and depression in rodent animal models (7,(13)(14)(15). We therefore tested the hypothesis that injecting ANA-12 into mice would predict efficient anxiolytic and antidepressant properties of the compound.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…BDNF and/or mRNA expression mPFC, AMY, substantia nigra, VTA Fanous et al 76 Reduced social behavior BDNF VTA Fanous et al 77 Reduced saccharin intake Furay et al 66 Increased cocaine self-administration…”
mentioning
confidence: 99%